Brand Reputation in the Age of AI: Impact of AI-Driven Customer Interaction, Social Media Engagement, and Sustainability Messaging on Consumer Trust and Purchase Intention - Jesus, Jiomarie B.; Besario, Ma. Rosalina A.; Bueno, Niña Lyn E.; Bonghanoy, Charito L.; Navaja, Rocel I.; Basilisco, Genessa L.; Sumilhig, Jeffy M.; Ople-Alviola, Chesa (International Review of Management and Marketing, 2025)
The rapid advancement of artificial intelligence (AI) has significantly transformed digital branding, necessitating a deeper investigation into how AI- driven strategies influence consumer behavior in emerging markets. This study examined the impact of AI-driven customer interaction, social media engagement, and sustainability messaging on brand trust and purchase intention, with brand trust hypothesized as a mediating variable. A descriptive- correlational design was employed, using structured questionnaires distributed to 600 digitally active consumers in Metro Cebu. Data analysis included Pearson correlation, multiple regression, and mediation analysis via bootstrapping to test the proposed relationships. Results revealed that all three digital branding strategies significantly predicted brand trust, which in turn was the strongest predictor of purchase intention; mediation analysis confirmed the critical role of trust in translating digital interactions into consumer decisions. These findings offer practical implications for marketers aiming to build sustainable brand reputations in AI-intensive environments, emphasizing the integration of personalization, ethical messaging, and trust-building as key components of future-ready digital branding models.